Neglecting justice? Exploring Scottish convictions for ill-treatment and wilful neglect. Issue 4 (10th August 2015) - Godwin, Christopher; Mackay, Kathryn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the perceived low number of Scottish criminal convictions in cases of ill-treatment or wilful neglect of adults where the victims experienced mental disorder, and/or incapacity. Human rights and anti-discrimination legislation are drawn upon to consider whether victims are gaining equality of access to justice through the charging and conviction of those who commit these offences. Design/methodology/approach – The paper uses the concept of parity of participation to first set out the wider legal framework in which access of justice takes place and to try to determine how it may be working in practice. Second the paper explores Scottish guidance, research and case law in relation ill-treatment or wilful neglect to evaluate the seeming lack of progress towards criminal convictions. Findings – Whilst the legal framework, at least on paper, appears to promote equality of access to justice, little is known about how it is working in practice; in particular whether cultural barriers to participation are being addressed. Evaluation of Scottish statistical data on cases of ill-treatment and wilful neglect revealed a small number of cases progressing to court though there were challenges in constructing a pathway from charges to convictions. There also appeared to be no Scottish legal opinions published in connection with these cases. In addition lack of research means that little is known about why cases progress, and how victims might be being supported through the process. Research limitations/implications – It is suggested that these gaps in information, in comparison to England and Wales, might be hindering practice. In particular the apparent lack of operational definitions for ill-treatment and wilful neglect in Scotland may reduce the use of this type of criminal offence. As such criminal offences embedded within civil mental health and mental capacity legislation may currently be hidden in plain sight. The human rights consequences of the issues raised in this paper are argued as significant. Research is needed to fill these gaps and inform future guidance and training. Practical implications – Improved Scottish guidance and publicity of this issue is required. Local inter-agency discussions and training could develop a better understanding of how these offences have been defined and how disabled people might be supported through the legal processes. The Scottish publication of statistical information for charging and convictions might usefully record these offences separately to give them a greater public profile in the future. Originality/value – This paper highlights the dearth of publicly available information on the number and nature of Scottish prosecutions for ill-treatment or wilful neglect. It suggest ways in how this might be addressed.